Implementation of Wordwall Interactive Media to Increase Enthusiasm and Participation of Grade IV Students of SDN Kaliputih in Jawa language Learning - Subur Widadi; Subuh Anggoro (UM Purwokerto Press, 2025)
This study aims to describe the implementation of Wordwall interactive media to enhance the enthusiasm and participation of fourth-grade students at SDN Kaliputih in Javanese language learning. The research employed a qualitative approach with data collected through observation, interviews, and documentation. The subjects of the study were fourth-grade students who participated in Javanese language lessons using Wordwall as a learning tool. The data were analyzed descriptively to observe changes in student interest and engagement before and after the media was applied. The findings revealed that the use of Wordwall significantly improved students’ enthusiasm and active participation in Javanese language learning. Students became more enthusiastic, responsive, and involved in the learning process. The engaging visuals and interactivity provided by Wordwall made the learning experience more enjoyable and less monotonous, thereby increasing the effectiveness of the teaching and learning process. This study highlights that digital interactive media like Wordwall can serve as an innovative learning strategy to support the preservation of local languages at the elementary school level.